Memória bibliográfica do Serviço Social junto à biblioteca do Instituto de Psicologia da UFRGS - Coser, Elise Maria Di Domenico (2014)
This dissertation discusses about the record and dissemination of the bibliographical memory of social work in the Library of the Institute of Psychology at UFRGS (Federal University of Rio Grande do Sul). For many centuries, the library has been considered as the designated place to store, organize, disseminate and preserve registered information. This way, the library is recognized to be a space for memory, which utilizes technology towards the democratization of knowledge, which is also where the dissertation’s researcher works. This study is justified due to the lack of digital data on Social Work memory, concerning the bibliographical aspect at UFRGS (Federal University of Rio Grande do Sul). As theoretical categories, social memory and the library are considered as memory environments. This quantitative and qualitative research utilizes documental research from the university’s data base (Sabi), analyzing the existing library collection from 2009 to 2012, which is when the Social Work course was established at the university. During this documental research, 356 book titles and 41 journals were identified. To analize the obtained data from the identified books and journals, it was utilized the content analysis and statistical treatment through frequency distribution. A blog was created at the end of this investigation, which was entitled: The Bibliographical Memory of Social Work as a digital environment for bibliographical memory.